2020
DOI: 10.21203/rs.3.rs-31556/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic Inflammatory Cytokines Associate With SARS-COV-2 Viral Shedding Time in Covid-19 Inpatients

Abstract: Background: Since December 2019, coronavirus disease 2019 (COVID-19), as an infectious disease with cytokine storm, has become an emerging global challenge. To assess the duration of SARS-COV-2 viral shedding and associated risk factors in COVID-19 patients.Methods: COVID-19 patients with interleukin (IL)-1b, soluble interleukin-2 receptor (sIL-2R), IL-6, IL-8, IL-10 and tumor necrosis factor (TNF)-α cytokines data consecutively admitted to Tongji Hospital from January 27, 2020 through February 5, 2020 were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…20 studies evaluated duration of viral RNA shedding based on disease severity. 13 of these studies reported longer duration of viral shedding in patients with severe illness than in those with non-severe illness, 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 whereas five studies in upper respiratory tract samples 16 , 18 , 35 , 36 , 37 and one study in stool samples 38 reported similar shedding durations according to disease severity. One study reported shorter duration of viral shedding in moderate to severe illness than in mild to moderate illness.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…20 studies evaluated duration of viral RNA shedding based on disease severity. 13 of these studies reported longer duration of viral shedding in patients with severe illness than in those with non-severe illness, 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 whereas five studies in upper respiratory tract samples 16 , 18 , 35 , 36 , 37 and one study in stool samples 38 reported similar shedding durations according to disease severity. One study reported shorter duration of viral shedding in moderate to severe illness than in mild to moderate illness.…”
Section: Resultsmentioning
confidence: 98%
“…350 articles were retrieved for full-text review. After reviewing the eligibility criteria, 79 studies (5340 individuals) on SARS-CoV-2, 2 , 3 , 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations